BCAT1 Activates PI3K/AKT/mTOR Pathway and Contributes to the Angiogenesis and Tumorigenicity of Gastric Cancer - Shu, Xiong; Zhan, Pan-Pan; Sun, Li-Xin; Yu, Long; Liu, Jun; Sun, Li-Chao; Yang, Zhi-Hua; Ran, Yu-Liang; Sun, Yue-Min (Frontiers in Cell and Developmental Biology, 2021)
Background: Focusing on anti-angiogenesis may provide promising choices for treatment of gastric cancer (GC). This study aimed to investigate the mechanistic role of BCAT1 in the pathogenesis of GC, particularly in angiogenesis. Methods: Bioinformatics and clinical samples analysis were used to investigate the expression and potential mechanism of BCAT1 in GC. BGC823 cells with BCAT1 overexpression or silencing were induced by lentiviral transduction. Cell phenotypes and angiogenesis were evaluated. The relevant proteins were quantized by western blotting, immunohistochemistry, or immunofluorescence. Xenograft models were constructed to confirm the role of BCAT1 in vivo. Results: BCAT1 was overexpressed in GC patients and associated with lower survival. BCAT1 expression was correlated with proliferation-, invasion-, or angiogenesis-related marker expression and pathways. Silencing BCAT1 expression suppressed cell viability, colony formation, cycle progression, invasion, and angiogenesis of BGC823 cells, as well as the tumor growth of xenograft models, whereas overexpressing BCAT1 had the opposite results both in vitro and in vivo. Bioinformatics analysis and western blotting demonstrated that BCAT1 activated the PI3K/AKT/mTOR pathway. The addition of LY294002 reversed the tumor growth induced by BCAT1 overexpression, further verifying this mechanism. Conclusions: BCAT1 might act as an oncogene by facilitating proliferation, invasion, and angiogenesis through activation of the PI3K/AKT/mTOR pathway. This finding could aid the optimization of anti-angiogenesis strategies.